Upper Limb Interactive Weightless Technology-Aided Intervention and Assessment Picks Out Motor Skills Improvement in Parkinson's Disease: A Pilot Study - Fundarò, Cira; Cavalieri, Carlo; Pinna, Gian Domenico; Giardini, Anna; Mancini, Francesca; Casale, Roberto (Frontiers in Neurology, 2020)
Background In Parkinson’s disease, reaching movements are conditioned by motor planning and execution deficiency. Recently, rehabilitation aided by high technological devices have been employed for Parkinson’s Disease. Objective We aimed 1- to investigate the changes in upper limb motor performances in a Parkinson’s Disease patient’s sample after a training with an exoskeleton device in an augmented feedback environment; 2-to highlight differences by motor parameters (performance, speed and movement accuracy) and by type of movement (simple or complex); 3-to evaluate movement improvements by means of UPDRS II-III. Methods Observational pilot study. 20 right-handed Parkinson's Disease patients, Hohen &Yahr 2, Mini Mental State Examination >24 were evaluated. All patients underwent a 5-day/week sessions for 4 weeks, 30 minutes for each arm; the training was performed with 12 exercises (single and multi-joints, horizontal and vertical movements). All the patients were assessed by means of UPDRS II-III and the evaluation tests provided by the device’s software: a simple movement, “vertical capture”, a complex movement “horizontal capture”. For each test we analysed reached targets percentage, movement execution time, accuracy. Results After training a significant improvement of accuracy and speed for simple movement on the dominant arm, of reached targets and speed for complex movement on both sides were shown. UPDRS II and III improved significantly after training. Conclusions In our study, a motor training aided by high technological device improves motor parameters and highlights differences between type of movement (simple or complex) and between movement parameters (speed and accuracy) in a Parkinson’s Disease patients’ sample.